(untitled) (Research, Society and Development, 2022)
This is an Integrative Literature Review where we sought to identify in the scientific literature studies on the administrative competences of nurses in times of crisis. The research was carried out in the following databases: MEDLINE, BDENF, LILACS, IBECS. Collects SUS, PAHO-IRIS through the VHL and CAPES Portal, in the time frame from 2019 to 2022, where 211 articles were found, however, after applying the inclusion and exclusion criteria, the final sample was left with six studies that were distributed according to its title, author and year of publication, journal and impact factor and the mentioned management skills. Data analysis allowed us to identify which management strategies are used by nurses in times of crisis. The study leads us to conclude that nursing is a profession that holds and applies soft skils and hard skills during its work process, which highlights the nurse’s managerial role.